Determination of the foraging behaviour and blood meal source of malaria vector mosquitoes in Trincomalee District of Sri Lanka using a multiplex real time polymerase chain reaction assay. (December 2016) - Gunathilaka, Nayana; Denipitiya, Thanuja; Hapugoda, Menaka; Abeyewickreme, Wimaladharma; Wickremasinghe, Rajitha
Abstract Background Studies of host preference patterns in blood-feeding anopheline mosquitoes are crucial to incriminating malaria vectors. However, little information is available on host preferences ofAnopheles mosquitoes in Sri Lanka. Methods AdultAnopheles mosquitoes were collected from five selected sentinel sites in Trincomalee District during June–September 2011. Each blood-fed mosquito was processed on filter papers. DNA was extracted using the dried blood meal protocol of the QIAmp DNA mini kit. A multiplexed, real-time PCR assay targeting eight animals was developed for two panels to identify the host meal ofAnopheles . Human blood index (HBI), forage ratio (FR) and host feeding index (HFI) were calculated. Results A total of 280 field-caught, freshly engorged female mosquitoes belonging to 12 anopheline species were analysed. The overall HBI and HFI in the present study were low indicating that humans were not the preferred host for the tested anopheline species. Nevertheless, a small proportion engorgedAnopheles aconitus, Anopheles culicifacies, Anopheles barbirostris, Anopheles annularis, Anopheles subpictus, Anopheles peditaeniatus, Anopheles pseudojamesi, andAnopheles barbumbrosus contained human blood. Conclusion The presence of human blood in mosquito species indicates the possibility of them transmitting malaria. Further studies on vector competence are needed to determine the role of each of the above anopheline species as efficient vectors of malaria.